Large area quantum dot luminescent solar concentrators for use with dye-sensitised solar cells - EVANS, RACHEL; GOUNKO, IOURI; PURCELL-MILTON, FINN (My University, 2018)
Luminescent solar concentrators (LSCs) have the potential to significantly contribute to solar energy harvesting strategies in the built environment. For the practical realisation of LSC technology, the ability to create large area devices, which contain considerable volumes of high quality luminescent species, is paramount. Here, we report the development of large area (90 cm2 top face), planar LSCs doped with green-emitting CdSe@ZnS/ZnS core–shell quantum dots (QD) with a composition gradient shell. The champion LSC demonstrates an optical efficiency of 1.2%, for a geometric factor of 7.9, under full spectrum illumination (AM1.5G). It was observed that inhomogeneity in the edge emission is a feature of large area devices and that an appropriate measurement geometry should be used to account for this when determining the optical efficiency. The LSCs exhibit excellent optical stability under accelerated testing conditions and display reasonably low optical reabsorption losses. Proof-of-principle integration of the QD-LSC with a planar, thin strip DSSC is demonstrated to generate an enhanced photocurrent. These results not only highlight the promise of composition gradient shell QDs for the practical realisation of large area LSCs, but indicate that we should look beyond conventional silicon cells and towards emerging photovoltaic (PV) technologies for the design of hybrid LSC-PV systems for the urban environment.